(3MGTjI YeGO Hf eMeO GdaGQSi Ydi MGTjI GdSjO GdTQjas - (3YeGO Hf eMeO Hf jMji Hf Ydj Hf GdaGSis; (3GdLQLGfj , Ydj Hf eMeO Hf Ydj GdSjO GdTQja GdLQLGfj, GdTQja GdLQLGfj,J (B816 (3g` s
(3ChdgG (B:s
(3hHYO aEfi Chdi Ndb Gddg Gdhdi YeGO Hf jMji Hf Ydi GdaGQSi s
(3BNQgG (B:s
(3CeG EPG cGf HjfgeG JbGHd GdYOe hGdedcI ajchf GdJchf CNU s
(3GdfSNI HgG MhGTs
(3cJGH GdTeSjI ai GdefWb dfLe GdOjf YeQ Hf Ydi GdbRhjfi GdcGHJis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs